Extraction and characterization of proteins present in concentrates from quality protein maize (QPM) - Garrido Balam, Mariel; Chel Guerrero, Luis Antonio; Castellanos Ruelas, Arturo Francisco; Moguel Ordoñez, Yolanda; Betancur Ancona, David Abram (Revista Colombiana de Investigaciones Agroindustriales, 2023)
Quality protein maize (QPM) represents an alternative protein source for food. This work aims to characterize fractions, molecular weights, and thermal stability of the proteins present in QPM protein concentrates obtained by isoelectric precipitation. Flours from two treatments, non-nixtamalized and nixtamalized, as well as three types of maize varieties: Sac Beh (QPM white), Chichén Itzá (QPM yellow), and Blanco Uxmal (control), were obtained. The experiment was conducted using a bifactorial 2x3 design. Four isoelectric precipitation pHs were evaluated, having the highest yield and maximum protein precipitation at pH 2,5 at 4 °C. The relative protein fractions in the maize varieties in both treatments showed more elevated amounts of prolamins (PR) and glutelins (GT) compared to the control. All QPM showed higher GT and lower PR. The denaturing electrophoretic profile (SDS-PAGE) showed molecular weights for the concentrates ranging from 17,6 to 225 kDa (non-nixtamalized), from 12,9 to 132,2 kDa (nixtamalized), and from the fractions with weights from 10,2 to 220,7 kDa. The thermograms showed a change in thermal stability in the concentrates from non-nixtamalized flour; there were no thermal transitions in the nixtamalized ones due to the denaturation of the proteins when obtaining the samples during nixtamalization of all the varieties studied.